2018
DOI: 10.1002/2017jd028005
|View full text |Cite
|
Sign up to set email alerts
|

First Effort for Constructing a Direct Solar Radiation Data Set in China for Solar Energy Applications

Abstract: Accurate estimate of direct solar radiation is a prerequisite for the design of concentrated solar power thermal systems; however, direct radiation observations are very sparse compared to observations of routine meteorological variables. Therefore, this study developed a method for estimating daily direct radiation from routine observations, based mainly on a clear‐sky physical model to compute clear‐sky direct radiation and a parameterized formula to compute cloud transmittance from sunshine duration data. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Other statistical indicators include the following: the correlation coefficient (r), mean bias error (bias), root-mean-square error, and relative root-mean-square error. (Li et al, 2011;Tang et al, 2018). The observed trends in R s and R dir appear to be steeper (likely spurious) than the derived trends during the period 1970-1989 (Figures 1c1 and 1d1).…”
Section: Models Performancesmentioning
confidence: 78%
See 1 more Smart Citation
“…Other statistical indicators include the following: the correlation coefficient (r), mean bias error (bias), root-mean-square error, and relative root-mean-square error. (Li et al, 2011;Tang et al, 2018). The observed trends in R s and R dir appear to be steeper (likely spurious) than the derived trends during the period 1970-1989 (Figures 1c1 and 1d1).…”
Section: Models Performancesmentioning
confidence: 78%
“…The equations of R dir and R dif are regressed based on the observed direct and diffuse solar radiation from 16 CMA stations during the period 1994–2014. Analogously, the calculation formula for the monthly derived R dir data set is improved based on that for the derived R s data set (He et al, ; Tang et al, ; Yang et al, ), as shown in equation : Rdir/Rc_italicdir=a0+a1×)(n/N+a2×n/N2 Rc_italicdir=τc_italicdir×I00.25emitalicdt …”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the estimated SSR were validated against the observations measured at the 42 BSRN stations at both instantaneous and daily scales. To reduce the uncertainties induced by broken clouds, we validated the estimated instantaneous SSR against hourly mean observed ones centered on the time of satellite overpass, according to the suggestion of Wang and Pinker (2009). To examine the effect of different spatial resolutions on the accuracy of our SSR estimates, in addition to the 10 km spatial resolution, we also evaluated our estimated SSR at spatial resolutions of 30, 50, 70, 90 and 110 km, derived by averaging the SSR values observed at the original scale of 10 km.…”
Section: Validation Of Estimated Ssr Against Observations At Bsrn Stamentioning
confidence: 99%
“…Daily global solar radiation (DGSR), as the major energy source of the Earth, plays a key role in the terrestrial radiation balance, energy exchange, hydrological cycle, photosynthesis, and the formation of weather and climate (Cooter & Dhakhwa, 1996;Cline et al, 1998;Hoogenboom, 2000;Power, 2001;Pohlert, 2004;Wild, 2009). DGSR is also crucial for the utilization of solar energy through transformation of technologies (Wu et al, 2012(Wu et al, , 2016Tang et al, 2018;Prăvălie et al, 2019;Zou et al, 2019). In recent years, there has been an aggravation of air pollution in China induced by massive fossil fuel consumption and emissions coinciding with unfavorable weather conditions (Guo et al, 2016Lou et al, 2019;Yang, et al, 2018;Yang, Ye, et al, 2019;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, this has significantly modulated the change in surface solar radiation (Che et al, 2005;Guo et al, 2018;Wang et al, 2012Wang et al, , 2013Wang & Wild, 2016;Zheng et al, 2018;He & Wang, 2020;Yang et al, 2020), while on the other hand, it has led to solar radiation becoming one of the fastest-growing and important sources of clean and renewable energy. Therefore, solar radiation is a topic that has attracted broad and increasing attention in China (Che et al, 2005;Sun et al, 2016;Li et al, 2017;Song et al, 2019;Tang et al, 2016Tang et al, , 2018Liu et al, 2019;He & Wang et al, © 2020 The Authors. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.…”
Section: Introductionmentioning
confidence: 99%